2019
DOI: 10.18632/oncotarget.27187
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of HOPX is critically involved in aggressive phenotypes and patient prognosis in papillary thyroid cancer

Abstract: HOPX is involved in multiple organ development and acts as a tumor suppressor in various cancers. Epigenetic silencing of HOPX via its promoter methylation has been shown frequent and cancer-specific in human cancers. The proliferation of thyroid cancer cells and cancer progression are strongly influenced by epigenetic alterations as well as genetic changes. Papillary thyroid cancer (PTC) comprises the vast majority of thyroid cancers and exhibits slow progression. However, ~10% of patients still show disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…25 In addition, Ooizumi et al indicated that HOPX is silenced by promoter DNA hypermethylation in papillary thyroid cancer. 26 Our data verified that promoter region of HOPX in CpG islands exhibited higher methylation in four breast cancer cell lines except SKBR3, which was consistent with previous study. 25 In addition, the expression of HOPX was downregulated in MCF-7 and MDA-MB-468 cells, indicating that the epigenetic silencing is involved in suppression of HOPX expression.…”
Section: Discussionsupporting
confidence: 92%
“…25 In addition, Ooizumi et al indicated that HOPX is silenced by promoter DNA hypermethylation in papillary thyroid cancer. 26 Our data verified that promoter region of HOPX in CpG islands exhibited higher methylation in four breast cancer cell lines except SKBR3, which was consistent with previous study. 25 In addition, the expression of HOPX was downregulated in MCF-7 and MDA-MB-468 cells, indicating that the epigenetic silencing is involved in suppression of HOPX expression.…”
Section: Discussionsupporting
confidence: 92%
“…Loss of HOPX expression as a result of promoter hypermethylation has clinical significance because in patients with gastric and colorectal cancer, the methylation status has been linked to a worse prognosis [ 55 , 61 ] and patients with strong HOPX expression in lung cancer have a considerably longer survival [ 56 ]. Epigenetic suppression of HOPX by promoter methylation plays a critical role in aggressive phenotypes in papillary thyroid cancer and is correlated with a poor prognosis of patients [ 71 ].…”
Section: Hopx In Carcinogenesismentioning
confidence: 99%
“…In differentiated thyroid cancer, hypermethylation of HOPX-β was associated with poor survival [58]. Ooizumi et al [59] found that HOPX promoter methylation resulted in aggressive phenotype in Papillary thyroid cancer, while forced HOPX expression suppressed cell proliferation, invasive activities, and anchorage-independent growth in vitro. These evidences suggest that the HOPX plays a role as a tumor suppressor gene in solid tumors.…”
Section: Solid Tumorsmentioning
confidence: 99%